Effect of geographical directions, height and the color of yellow traps in capture of Mediterranean fruit fly, Ceratitis capitata (Wiedemann, 1824) in citrus orchards - Amir Hossein TOORANI; Habib ABBASIPOUR (Acta Agriculturae Slovenica, 2017)
Mediterranean fruit fly, Ceratitis capitata (Wiedemann, 1824) (Dip.: Tephritidae) is one of the most destructive agricultural pests in the world. To replace chemical control methods, as well as the timing of the peak population of Mediterranean fruit fly, the yellow sticky vertical traps were used in this study. The research was carried out in some citrus orchards of various cities of Mazandaran province of Iran, during the four months from August to November 2016. To determine the best type of yellow color to trap this fly, four types of yellow colors with measured wavelength of reflection, including the fluorescent yellow (538 nm), lemon yellow (574 nm), yellow (602 nm) and amber yellow (641 nm), were used. Also, to determine the best geographical direction and appropriate height for installation of yellow cards, four cardinal directions and five different heights of 1, 1.5, 2, 2.5 and 3 m above ground level were determined and the cards were installed. The results of mean comparison of captured flies in different treatments showed that there are significant differences between all of them. The results indicated that the fluorescent yellow, heights of 1.5 and 2 m, the south direction, and month October had the highest number of capture in yellow cards.